Unleashing the Power of Psychological Capital: A Catalyst for Enhanced Work Performance in the Post-COVID Landscape via Job Satisfaction Mediation - Setioningtyas, Widhayani Puri; Fodor, Zita Julia; Dunay, Anna (Acta Carolus Robertus, 2025)
In the post-pandemic landscape of Indonesia's Small and Medium Enterprises (SMEs) sector, our study delves into the intricate dynamics of employee work performance. We focus on Psychological Capital (PsyCap) and its impact on Individual Work Performance (IWP), comprising Task Performance (TP), Contextual Performance (CP), and Counter-Productive Work Behavior (CPWB), with a particular emphasis on the mediating role of Job Satisfaction (JS). We conducted our research with a diverse sample of 345 participants drawn from various SME sectors, providing a comprehensive insight into employees' behavior across industries. Our analysis utilized the AMOS-Structural Equation Modeling (SEM) approach. The results illuminated a positive correlation between PsyCap and IWP in terms of Task Performance (TP) and Job Satisfaction (JS). However, no significant relationship was found between PsyCap and Contextual Performance (CP) or Counterproductive Work Behavior (CPWB). Furthermore, our study unveiled the mediation role of Job Satisfaction (JS) in these relationships. JS was found to partially mediate the connection between PsyCap and IWP-TP, while it fully mediated the link between PsyCap and IWP-CP. However, Job Satisfaction (JS) did not mediate the relationship between PsyCap and IWP-CPWB. These findings underscore the significance of nurturing Psychological Capital (PsyCap) to enhance Task Performance, Contextual Performance, and Job Satisfaction among employees. We recommend future investigations to explore PsyCap development further, considering variables like demographics and social capital, as they could hold the key to optimizing employee performance in SMEs.
Keywords: psychological capital; job satisfaction; task performance; contextual performance; counterproductive work behavior